1993
DOI: 10.1007/bf00685681
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical evaluation of [SP-4-3(R)]-[1,1-cyclobutanedicarboxylato(2-)](2-methyl-1,4-butanediamine-N,N 1) platinum in patients with metastatic solid tumors

Abstract: The development of clinically useful drugs is a priority of clinical cancer research. CI-973, [SP-4-3(R)]-[1,1-cyclobutanedicarboxylato(2-)](2-methyl-1,4- butanediamine-N,N1) platinum, has been shown in preclinical murine and human tumor models to have activity equivalent or superior to that of cisplatin and carboplatin and to exert activity against cisplatin-resistant cell lines. In addition, preclinical testing suggests a reduced toxicity profile for CI-973 as compared with currently available drugs, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…73, 74 Two Phase I trials were completed with sebriplatin as a daily ¥ 5 and a once monthly IV infusion. 75,76 In the multiple dosing trial neutropenia was the DLT, but was rapidly recoverable, with mild/infrequent vomiting and nausea. 75 The MTD was determined to be 40-50 mg m -2 from which a Phase II dose of 30 mg m -2 day -1 for 5 days was recommended.…”
Section: Sebriplatinmentioning
confidence: 99%
See 1 more Smart Citation
“…73, 74 Two Phase I trials were completed with sebriplatin as a daily ¥ 5 and a once monthly IV infusion. 75,76 In the multiple dosing trial neutropenia was the DLT, but was rapidly recoverable, with mild/infrequent vomiting and nausea. 75 The MTD was determined to be 40-50 mg m -2 from which a Phase II dose of 30 mg m -2 day -1 for 5 days was recommended.…”
Section: Sebriplatinmentioning
confidence: 99%
“…75 In the once monthly trial a MTD of 290 mg m -2 was determined with granulocytopenia as the DLT for patients previously untreated with platinum, radiation or stem cell toxin therapy, and a MTD of 230 mg m -2 for those who had previously been treated with at least one of these regimes. 76 Doses of 230 and 190 mg m -2 were recommended for Phase II trials in these groups of patients.…”
Section: Sebriplatinmentioning
confidence: 99%
“…There was also no evidence of neurotoxicity. Phase I studies in patients with solid tumors established that neutropenia was the doselimiting toxicity, and confirmed that CI-973 was not seriously nephrotoxic, neurotoxic, or ototoxic (7)(8)(9). Furthermore, it did not cause severe thrombocytopenia, even in patients who developed Grade IV neutropenia.…”
Section: Discussionmentioning
confidence: 82%
“…in vitro and in vivo (4)(5)(6). Phase I studies in patients with solid tumors indicate that, unlike cisplatin, CI-973 does not appear to cause serious renal toxicity, neurotoxicity, or ototoxicity (7)(8)(9). CI-973 is myelosuppressive, causing dose-limiting neutropenia, but is not associated with the dose-limiting thrombocytopenia characteristic of carboplatin therapy.…”
mentioning
confidence: 99%
“…CI-973, a water-soluble platinum diamine complex, showed activity equivalent or superior to that of cisplatin and carboplatin and was active against cisplatin-resistant tumors in phase I trials, with lower side effects [26]. In a phase II trial on 26 previously treated patients with MBC, CI-973 was administered intravenously at a dose of 230 mg/m 2 over 30 min at 3-week intervals.…”
Section: Experience With Single-agent Therapymentioning
confidence: 99%